Analisis Kemampuan Berpikir Kritis Ditinjau Pada Aspek Sociomathematical Norms - Wiyono, Ikhsannuddin; Maarif, Samsul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study intends to describe students’ critical thinking skills interms of socio-mathematic norms that students have when learningmathematics in class. The subjects of this study were students of classXI SMA 66 foundatio of Jakarta. The research method used isdescriptive qualitative method. This study used a test on the subjectmatter of the Three Variable Linear Equation System (SPLTV) and theLinear Program to examine critical thinking skills, as well as sociomathematic norm questionnaires and interviews. Based on the resultsof the study, there were 37 samples who worked on the test questionsand filled out questionnaires. From this, 6 informants wereinterviewed, consisting of 2 informants with high levels of criticalthinking skills and socionatenatic norms, 2 medium categoryinformants, and 2 low category informants.